The Old Turkic toponym Qadïrqan and its possible equivalents in modern languages of the Sayano-Altai region - Simchit, Kyzyl-Maadyr A. (The New Research of Tuva, 2018)
The article examines the Old Turkic toponym ‘qadïrqan’ and its possible correspondences in modern languages of the Sayano-Altai region. The author suggests the lexeme ‘qadïrqan’ can be compared with ‘хайыракан’ (hairaqan), common in some forms or meanings in certain modern languages of the region. There are several mountains whose names contain the component ‘hayyrakan’ in Tuva, and all of them have sacred meaning for Tuvans. We provide an in-depth overview of how the word is used in Tuvan folklore texts related to shamanistic beliefs, etc. In general, the lexeme is widely used as a euphemism for a bear in the Tuvan language. There is a theory that its origin is Mongolian. We, however, have proved that a parallel between the Old Turkic ‘qadïrqan’ and the ‘hayyrakan’ lexeme does have a solid basis, by comparing various forms and meanings of the word, or of its components, in a number of Turkic languages. A link between ‘qadïrqan’ and ‘hayyrakan’ is possible due to phonetic laws. The transition of the intervocalic -д- / -й- (-d- / -y-) in the first syllable is a typical feature of the Old Turkic, and possibly Mongolian, languages. A semantic comparison is also possible. The Old Turkic ‘qadïrqan’ and the ‘hayyrakan’ form share a direct link to mountains. The motivation for such a respectful attitude to the mountains was undoubtedly important not only for the Mongols, but for the Old Turks and ancestors of the Tuvans in the epoch of feudalism. We presume that the Old Turkic toponym ‘qadïrqan’ was borrowed by the Mongolian tribes in the Middle Ages, during the period of Mongol rule. From their use, it passed to some languages of the Turkic-Mongolian contact zone, including the Tuvan language, where it firmly and deeply took root in its vocabulary.